2011
DOI: 10.1016/j.yhbeh.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in the medial preoptic area facilitates male sexual behavior in the rat

Abstract: Oxytocin (OT) is a versatile neuropeptide that is involved in a variety of mammalian behaviors, and its role in reproductive function and behavior has been well established. The majority of pharmacological studies of the effects of OT on male sexual behavior have focused on the paraventricular nucleus (PVN), ventral tegmental area (VTA), hippocampus, and amygdala. Less attention has been given to the medial preoptic area (MPOA), a major integrative site for male sexual behavior. The present study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 41 publications
1
40
0
1
Order By: Relevance
“…We previously demonstrated that ICV administration of OTA reduces mating frequency in male prairie voles (Johnson et al, 2016). Taken together, these data suggest that OTRs in other nuclei modulate sexual behavior in male prairie voles, consistent with findings in rats (Argiolas and Melis, 2013; Gil et al, 2011). Importantly, these results suggest that any significant differences in Fos-ir between treatment groups are not due to differences in any of the analyzed sociosexual behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…We previously demonstrated that ICV administration of OTA reduces mating frequency in male prairie voles (Johnson et al, 2016). Taken together, these data suggest that OTRs in other nuclei modulate sexual behavior in male prairie voles, consistent with findings in rats (Argiolas and Melis, 2013; Gil et al, 2011). Importantly, these results suggest that any significant differences in Fos-ir between treatment groups are not due to differences in any of the analyzed sociosexual behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Each barrel was attached by polyethylene tubing (PE-10) to separate Hamilton syringes (2 l) and injections were made over 1 min using a microinjection pump (Nexus 3000, Chemyx Inc., Houston, TX, USA). The dose of oxytocin injected into the NAcSh was within the range effective doses of oxytocin used in previous studies (Gu and Yu, 2007;Baracz et al, 2011;Gil et al, 2011;Sanna et al, 2012).…”
Section: Intracranial Injectionsmentioning
confidence: 60%
“…Work from our lab on an ovariectomized female rat model found fewer effects of age and E2 on nonapeptide gene expression in the POA (Yin et al, 2015), suggesting a greater sensitivity of the male than the female brain. Oxytocin in the POA facilitates sexual behavior in males, and this undergoes age-related impairments (Gil et al, 2011). Furthermore, oxytocin colocalizes with the p450 aromatase enzyme in the male POA (El-Emam Dief et al, 2013), suggesting the capacity of these cells to convert testosterone to estradiol.…”
Section: Discussionmentioning
confidence: 99%